2016
DOI: 10.1080/15402002.2016.1253013
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Cognition: A Mediating Role of Efficient Sleep

Abstract: Objective Physical activity benefits executive control, but the mechanism through which this benefit occurs is unclear. Sleep is a candidate mechanism given that it improves with exercise and has restorative effects on the prefrontal cortex. The present cross-sectional study examined the mediating role of sleep in the relationship between physical activity and executive control in young and older adults. Participants Young (n = 59) and older (n = 53) community-dwelling adults ages 21–30 and 55–80. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 77 publications
(122 reference statements)
7
70
3
5
Order By: Relevance
“…This null finding aligns with a recent paper also drawn from this study cohort (Falck et al, ); however, it stands in contrast to the conclusions of a narrative review of observational and experimental studies (Buman & King, ) and to the findings of a meta‐analysis of exercise interventions (Kredlow et al, ). Most relevant, our lack of between‐subject associations differs from a study of younger and older adults, whose sleep and PA were measured via a SenseWear® Armband for 7 days (Wilckens, Erickson, & Wheeler, ). Specifically, this previous study detected a modest association (standardized beta = 0.23) between sleep efficiency and PA, and therefore much larger samples than the current one may be required to reliably detect the association with statistical significance.…”
Section: Discussionmentioning
confidence: 88%
“…This null finding aligns with a recent paper also drawn from this study cohort (Falck et al, ); however, it stands in contrast to the conclusions of a narrative review of observational and experimental studies (Buman & King, ) and to the findings of a meta‐analysis of exercise interventions (Kredlow et al, ). Most relevant, our lack of between‐subject associations differs from a study of younger and older adults, whose sleep and PA were measured via a SenseWear® Armband for 7 days (Wilckens, Erickson, & Wheeler, ). Specifically, this previous study detected a modest association (standardized beta = 0.23) between sleep efficiency and PA, and therefore much larger samples than the current one may be required to reliably detect the association with statistical significance.…”
Section: Discussionmentioning
confidence: 88%
“…Changes in sleep quality, for example, are linked to both cognition and to PA. However, only one study to date (Wilckens et al, in press) has combined all three variables in a statistical model to test whether sleep can account for the relationship between PA and cognitive performance—the results of this initial study suggest that it can. Similarly, mood is linked both to cognitive performance and PA.…”
Section: Discussionmentioning
confidence: 98%
“…Both PA and sleep were objectively measured with accelerometry. Wilckens et al (in press) found that PA energy expenditure was positively associated with sleep efficiency, as well as executive functioning and processing speed. Further, sleep efficiency statistically mediated the relationship between PA and several measures of cognitive performance.…”
Section: Level 3: Behavioral and Socioemotional Mechanismsmentioning
confidence: 93%
See 1 more Smart Citation
“…We still have much to learn about the mediators of these effects and moderators of the effects . However, there is clear recognition that the effects of physical activity extend beyond cognitive function and how physical activity‐induced changes to the brain mediate changes in these and other behavioral outcomes is an important avenue for future research.…”
Section: Neuroimaging and Neuromodulation Research In Exercise And Eamentioning
confidence: 99%